Strengthening Health Systems in Humanitarian Settings: Multi-Stakeholder Insights on Contraception and Postabortion Care Programs in the Democratic Republic of Congo and Somalia - Tran, Nguyen Toan; Meyers, Janet; Malilo, Bibiche; Chabo, Julien; Muselemu, Jean-Baptiste; Riziki, Bienvenu; Libonga, Patrick; Shire, Abdikani; Had, Hussein; Ali, Mohamed; Arab, Mohamed Abdi; Da'ar, Jama Mohamed; et al. (Frontiers in Global Women's Health, 2021)
Background: In humanitarian settings, strengthening health systems while responding to the health needs of crisis-affected populations is challenging and marked with evidence gaps. Drawing from a decade of family planning and postabortion care programming in humanitarian settings, this paper aims to identify strategic components that contribute to health system strengthening in such contexts. Materials and Methods: A diverse range of key informants from North Kivu (Democratic Republic of Congo, DRC) and Puntland (Somalia), including female and male community members, adolescents and adults, healthcare providers, government and community leaders, participated in qualitative interviews, which applied the World Health Organization health system building blocks framework. Data were thematically analyzed according to this framework. Results: Findings from the focus group discussions (11 in DRC, 7 in Somalia) and key informant interviews (seven in DRC, four in Somalia) involving in total 54 female and 72 male participants across both countries indicate that health programs in humanitarian settings, such as Save the Children's initiative on family planning and postabortion care, could contribute to strengthening health systems by positively influencing national policies and guidance, strengthening local coordination mechanisms, capacitating the healthcare workforce with competency-based training and supportive supervision (benefiting facilities supported by the project and beyond), developing the capacity of Ministry of Health staff in the effective management of the supply chain, actively and creatively mobilizing the community to raise awareness and create demand, and providing quality and affordable services. Financial sustainability is challenged by the chronically limited healthcare expenditure experienced in both humanitarian contexts. Conclusions: In humanitarian settings, carefully designed healthcare interventions, such as those that address the family planning and postabortion care needs of crisis-affected populations, have the potential not only to increase access to essential services but also contribute to strengthening several components of the health system while increasing the government capacity, ownership, and accountability.